University asset management system (UniAMS) - Che Ali, Che Fuziah (2006)
This thesis studies, analyzes and develops a system to manage the implementation of procurement through quotation proposal and management of asset information at Advance Information Technology Institute (AITI) as a case study with ultimate aim that the system is to be used at Universiti Technologi Malaysia (UTM) in particular, and at Public Higher Learning Institute of Malaysia (IPTA) in general. This is because all IPTAs are covered by a circular and a letter of Treasury of Malaysia for instance Surat Pekeliling Perbendaharaan Bil.6 Tahun 1998 dan Pekeliling Perbendaharaan (PP) Bil. 2 Tahun 1991. University Asset Management System is a web-based application that was developed using object oriented approach while Hypertext Preprocessor (PHP) is used as a programming language, Multi-user Structured Query Language (mySQL) for database, Apache Web Server for the server and PhpMyAdmin as an editing tool for database. Through the University Asset Management System, activities of procurement through quotation proposal and management of asset can be administered online which involve user categories such as System Administrator, Applicant / Custodian, Approver, Administrator Officer, Quotation Assembler ,Quotation Committee, Administration Officer, Site Officer, Inspector, Building Property Office and Supplier. In general, University Asset Management System is a system that advocates managing information with more efficient, correct and accurate, uniform besides minimizing typing error/s due to typing are only done during the beginning of the process.